Type 1 gastric carcinoid tumor: another extrahepatic manifestation of hepatitis C virus infection? - Eser VARDARELİ and Tülay SARIÇAM and Serap IŞIKSOY and Hasan YAVUZ and Ayşegül ÖZAKYOL and Baybora KIRCALI (Turkish Journal of Gastroenterology, 2019)
-